Comparison of daily and monthly intra-urban thermal reactions based on LCZ classification using surface and air temperature data - Fricke, Cathy; Pongrácz, Rita; Unger, János (Geographica Pannonica, 2022)
Urban air (Ta) and surface (Ts) temperature patterns depend mainly on the surface cover conditions. WUDAPT methodology was used to create the local climate zone (LCZ) map of Szeged (Hungary) providing detailed information about the structure of the urban area. The seasonal and monthly variations of simultaneous measurements of Ta (urban network) and Ts (MODIS) in different LCZs were analysed for a four-year period. The results show that the largest differences between Ts and Ta values occur in late spring and summer. During the day, the monthly mean Ts was much higher than the mean Ta, while at night, the Ta exceeded the Ts in all LCZs. Linear statistical relationship was also analysed, which concluded that diurnal and nocturnal Ta and Ts are strongly correlated in all LCZs in Szeged.